MANAGERIAL ACCOUNTING–TWENTY YEARS FROM NOW. - Greer, Howard C. (The Accounting Review, 1954)
Abstract This article presents views of the author on information on managerial accounting twenty years from now as of January 1954. According to the author managerial accounting activities which now, as then, strike him as most likely to be productive include increased emphasis on what might be called "pre-accounting" studies-the preparation of budgets, the establishment of standards, etc. Secondly, greater attention to intensive primary analysis of costs and expenses, to provide more finely subdivided and carefully shaped "building blocks" for subsequent cost determination and performance evaluation. Then, closer study of the relationship between costs and prices, with particular attention to the distinction between recovery and out- of-pocket costs and contributions toward general overhead expenses. Finally, improved arrangement of financial statements, to clarify important internal and inter-statement relationships.